Dispositivo de encerramiento para mejorar las condiciones de temperatura, la Habitabilidad y confort para el crecimiento de aves de engorde de 1 a 8 días de nacidos en granjas de pequeña escala de Albán Cundinamarca - Loaiza Barajas, Lina María (Universidad Antonio Nariño, 2021)
This project will design a technologically efficient and portable modular system that senses the ambient temperature by means of a surface contact RTD type PT100 transducer to improve the habitation and growth conditions of broilers from 1 to 8 days old in small farms. scale, in a way that significantly influences the growth and welfare of these animals.